2013
DOI: 10.1021/bi401250a
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Zinc Finger and Flanking Basic Domains Represent the Minimal Region of the Human Immunodeficiency Virus Type-1 Nucleocapsid Protein for Targeting Chaperone Function

Abstract: The human immunodeficiency virus type-1 (HIV-1) nucleocapsid (NC) protein is a chaperone that facilitates nucleic acid conformational changes to form the most thermodynamically stable arrangement. The critical role of NC in many steps of the viral life cycle makes it an attractive therapeutic target. The chaperone activity of NC depends on its nucleic acid aggregating ability, duplex destabilizing activity and rapid on/off binding kinetics. During the minus-strand transfer step of reverse transcription, NC cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…TAR destabilization in our conditions was limited because NC destabilizes only three consecutive base pairs with high efficiency. However, the NC:nt ratio was significantly different in the two studies (1:7.5 versus 1:59) (Bernacchi et al 2002) and NC(1-55) has a greater destabilization capacity that NC(12-55) (Levin et al 2005;Vo et al 2009b;Mitra et al 2013). Finally, the extensive broadening of imino proton resonance does not necessarily indicate a loss of the corresponding base pair.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…TAR destabilization in our conditions was limited because NC destabilizes only three consecutive base pairs with high efficiency. However, the NC:nt ratio was significantly different in the two studies (1:7.5 versus 1:59) (Bernacchi et al 2002) and NC(1-55) has a greater destabilization capacity that NC(12-55) (Levin et al 2005;Vo et al 2009b;Mitra et al 2013). Finally, the extensive broadening of imino proton resonance does not necessarily indicate a loss of the corresponding base pair.…”
Section: Discussionmentioning
confidence: 76%
“…The relationship between binding polarity and the polarized destabilization of stem-loops may result from the lack of equivalence of the two zinc fingers, ZF1 and ZF2, with ZF1 more involved in the destabilization than ZF2. In contrast, ZF2 is involved in the specific recognition of guanine residues (Guo et al 2002;Heath et al 2003;Beltz et al 2005;Narayanan et al 2006;Hergott et al 2013;Mitra et al 2013). Binding polarity may therefore be responsible for the localization of ZF1 close to a double-stranded region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The highly basic nature of HIV-1 NC stems primarily from its a-helical N-terminal domain, and is the driving force behind NC's strong NA aggregation activity [4][5][6][7]. The Zn fingers each contain one or two aromatic residues that can interact with nucleobases via stacking interactions, and have been shown to promote duplex destabilization [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the NC mutant in which ZF1 has been duplicated (ZF1+ZF1) is more replication competent than mutants with zinc finger-swap (ZF2+ZF1) or with duplicated ZF2 (ZF2+ZF2)6. Several studies of ZF mutants revealed that ZF1 was more critical than ZF2 for the NC chaperone activity789. In addition, nucleic acid binding abilities of different NC domains have been analyzed and revealed that the absence of ZF2 (NC 1-35) did not reduce NC binding affinity, demonstrating that ZF1 provides the major contribution to DNA binding9.…”
mentioning
confidence: 99%